Discovery of the digger wasp genus Pseudoscolia Radoszkowski, 1876 (Hymenoptera: Crabronidae: Philanthinae: Pseudoscoliini) in Indian Sub-continent, with description of a new species - Saini, Varun (Zootaxa, 2024)
The digger wasp genus Pseudoscolia Radoszkowski, 1876 is newly reported from India with a new species: Pseudoscolia anuae Saini sp. nov. from the State of Haryana.